Analisis Pengaruh Kualitas Produk Terhadap Kepuasan Pelanggan pada Produk Komik PT Elex Media Komputindo (Studi Kasus Pada Komunitas Kolektor Komik Indonesia) - Suhada, Ferial (Prodi S1 Administrasi Bisnis Universitas Sangga Buana YPKP, 2025)
The purpose of this study is to determine the effect of product quality on customer satisfaction regarding comic products published by PT Elex Media Komputindo. This research was conducted using a quantitative method, with data collection through the distribution of questionnaires to a sample. The population in this study were members of the Indonesian Comic Collector Community who purchased comics published by PT Elex Media Komputindo within the last 6 months. The sample size in this study is 35 respondents selected using the accidental sampling method. The collected data will be processed and the hypothesis tested using a t-test. The results of the study indicate a significant relationship between product quality and satisfaction levels for the comic products of PT Elex Media Komputindo.